A review on the interview process with women victims of violence - Ayata Küçükbükücü, Ruşen (The Bulletin of Legal Medicine, 2025)
The phenomenon of “violence,” which is one of today’s major social issues, affects all age groups and genders in different ways. The commonly encountered phenomenon of “violence against women” has the power to profoundly impact women’s lives. These effects manifest differently in each woman and may lead to various reactions. Women subjected to violence may tend to conceal the violence and remain silent. Those who find it difficult to share their stories of violence may experience anxiety about seeking help and building trust. This situation is associated with the restrictions women face in living their individual lives freely in a patriarchal social structure. The ability of women who have been subjected to violence to share the violence they experienced, information about the perpetrator, the setting where the violence occurred, and the overall process is only possible when the interview is conducted by professionals who are experts in the field and capable of applying their interview skills effectively. This study is a review based on a literature analysis. It examines the key points to consider and the necessary skills during interviews conducted with women exposed to violence. The findings indicate that factors such as the appropriateness of the interview setting, the establishment of a trust-based relationship, the professional competencies of the interviewer, and allocating sufficient time for the interviews are important.
Keywords: woman; violence; interviewing